Improving the registration process in a healthcare facility with lean principles - Valentina Nino; Kenneth J. Martinez; Karina Gomez; David Claudio (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Process improvement in service industries, like the registration process in a hospital, can be achieved with the application of lean principles. In this specific case, lean principles were essential to analyze and improve patient satisfaction in a hospital in Montana. The clinics involved in the study included pediatrics (P), internal medicine (IM), and cardiology/pulmonary (CP). The purpose of this study was to address difficulties regarding patient satisfaction on the registration and check-in processes. Design/methodology/approach: Direct observations and patient surveys were initially made to understand the processes and identify the initial causes of dissatisfaction. A value stream map (VSM) was then used to break down even further the complexity of the patient flow. A Fishbone diagram and a concept map were completed to get to the root of the dissatisfaction. Findings: The information obtained from the lean tools showed that patients questioned the need for having a central registration in combination with the check-in process when this combination generates duplications of steps that cause unwanted delays. Several recommendations were explored by the engineering team to mitigate these delays and improve the registration process reducing the number of patients complaints by 40%. Practical implications: This project illustrated the application of Lean principles to resolve issues regarding a central registration format in a healthcare facility. Originality/value: A concept map was used as a tool that helps business organizations in the development of creative and new ways of looking and solving process deficiencies.
Keywords: 650; Lean principles; patient satisfaction; quality improvement; central registration